A monoclonal IgG anticardiolipin antibody from a patient with the antiphospholipid syndrome is thrombogenic in mice. - Olee, T (1996)
Antiphospholipid antibodies, including anticardiolipin antibodies (ACA), are strongly associated with recurrent thrombosis in patients with the antiphospholipid syndrome (APS). To date, reports about the binding specificities of ACA and their role(s) in causing and/or sustaining thrombosis in APS are conflicting and controversial. The plasmas of patients with APS, usually containing a mixture of autoantibodies, vary in binding specificity for different phospholipids/cofactors and vary in in vitro lupus anticoagulant activity. Although in vivo assays that allow assessment of the pathogenic procoagulant activity of patient autoantibodies have recently been developed, the complex nature of the mixed species prevented determination of the particular species responsible for in vivo thrombosis. We have generated two human IgG monoclonal ACA from an APS patient with recurrent thrombosis. Both bound to cardiolipin in the presence of 10% bovine serum, but not in its absence, and both were reactive against phosphatidic acid, but were nonreactive against purified human beta-2 glycoprotein 1, DNA, heparan sulfate, or four other test antigens. Both monoclonal autoantibodies lacked lupus anticoagulant activity and did not inhibit prothrombinase activity. Remarkably, one of the monoclonal antibodies has thrombogenic properties when tested in an in vivo mouse model. This finding provides the first direct evidence that a particular antiphospholipid antibody specificity may contribute to in vivo thrombosis.